2012
DOI: 10.1590/s1517-83822012000100001
|View full text |Cite
|
Sign up to set email alerts
|

Physiological studies on carboxymethyl cellulase formation by Aspergillus terreus DSM 826

Abstract: Physiological studies were conducted to determine the optimum cultural conditions for maximal carboxymethyl cellulase (CMCase) formation by Aspergillus terreus DSM 826. Shaking condition at 150 rpm is favorable for the production of CMCase from rice straw and sugar cane bagasse. The highest enzyme yield was obtained at the third day of incubation at 30 °C for both cases; however CMCase formation occurred at a broad range of pH values, with maximal formation of A. terreus DSM 826 CMCase at pH 4.5 and 5.0 when r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
2
10
1
Order By: Relevance
“…According to Jecu (2000), cellulase production at pH 7 yielding maximum production (9.85 IU/mL), which was obtained during this research (38.80 U/mL/min carboxymethyl cellulase, 10.89 U/mL/min exoglucanase). Whereas inoculum size of 15% exhibiting the maximum yield which is quite differ from the results of Abdel-Fatah et al (2012), reported 10% inoculums size for maximum yield. The urea is the cheap and good nitrogen source for production of cellulase enzyme by Aspergillus specie (as compare to other nitrogen sources so, utilizing urea as a nitrogen source yield maximum carboxymethyl cellulase, exoglucanase and protein production.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…According to Jecu (2000), cellulase production at pH 7 yielding maximum production (9.85 IU/mL), which was obtained during this research (38.80 U/mL/min carboxymethyl cellulase, 10.89 U/mL/min exoglucanase). Whereas inoculum size of 15% exhibiting the maximum yield which is quite differ from the results of Abdel-Fatah et al (2012), reported 10% inoculums size for maximum yield. The urea is the cheap and good nitrogen source for production of cellulase enzyme by Aspergillus specie (as compare to other nitrogen sources so, utilizing urea as a nitrogen source yield maximum carboxymethyl cellulase, exoglucanase and protein production.…”
Section: Discussioncontrasting
confidence: 79%
“…Almost all fungi of genus Aspergillus can synthesize cellulase. Aspergillus species are great producer of useful enzymes and have various importance in medicine, agriculture and food industry (Abdel-Fatah et al, 2012). Cellulases including CMCase enzymes are produced in submerged fermentation (SmF) as well as solid state (Substrate) fermentation (SSF).…”
mentioning
confidence: 99%
“…According to the study of Domingues et al (2000), Tween-80 influenced the morphology of Trichoderma reesei Rut C-30 as well as the enzyme production. The stimulatory effect of surfactants may be a consequence of its action on cell membranes causing increase in permeability by promoting the release of cell-bound enzymes (Abdel-Fatah et al 2012). On the other hand, Triton X-100 appeared to be the best surfactant for the production of cellulase in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Since the cellulose enzymes are used in a wide variety of industrial applications, the demand for more stable, highly active, and substrate specific enzymes is also growing rapidly (Shahzadi et al 2014). Cellulases are inducible enzymes and synthesized by a large diversity of microorganisms, including fungi and bacteria (Abdel-Fatah et al 2012). Accordingly, it is highly desirable to exploit new organisms capable of producing highly efficient cellulolytic enzymes and determine the most efficient method for producing these enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, bacterial cellulases can survive in harsh conditions of bioconversion processes, and also be less inhibited by the presence of material that has already been hydrolyzed (feedback inhibition) (Kadarmoidheen et al 2012). Therefore, the isolation and characterization of novel glycoside hydrolases from bacteria are now becoming widely exploited (Maki et al 2009;Abdel-Fatah et al 2012), and the cellulolytic property of some bacterial genera such as Clostridium (Yuan et al 2015), Cellulomonas (Kojima et al 2013), Pseudomonas (Huang et al 2012;Sheng et al 2012), Bacillus (Gaur and Tiwari 2015), and Streptomyces (Azzeddine et al 2013) has been widely reported. Athrobacter species are predominant members of culturable soil bacteria and can utilize a wide variety of organic compounds, such as aromatic hydrocarbons, nucleic acids and their degradation products, herbicides (Crocker et al 2000).…”
Section: Introductionmentioning
confidence: 99%